Global reliability evaluation of a high-pier long-span continuous RC rigid frame bridge subjected to multi-point and multi-component stochastic ground motions. Issue 164 (January 2023) - Liu, Zixin; Liu, Zhangjun; Ai, Qinghua; Ruan, Xinxin; Tan, Chunyuan
Abstract: High-pier long-span continuous RC rigid frame bridges would be more vulnerable to seismic spatial variability and multi-component nature due to their large geometric dimension. However, research on seismic performance of these bridges subjected to multi-point and multi-component ground motions is sparse. In this study, the unified expression of spectral decomposition integrating spectral representation method and proper orthogonal decomposition based on coherency function matrix is derived. Then the dimension-reduction representation is developed for sample realization of multi-point and multi-component non-stationary stochastic ground motions with merely three elementary random variables, which bypasses the challenges of high-dimensional randomness degree and huge computation expense faced by the Monte Carlo simulation scheme. Thereafter the accurate seismic response analysis of a high-pier long-span bridge is numerically scrutinized combining with the probability density evolution method to further expound the effectiveness of the dimension-reduction model. Finally, a heuristic global reliability evaluation strategy employing relative displacement angle of bridge pier segments as criterion is proposed inspired by the idea of equivalent extreme-value event. Benefiting from this, both the refined reliability evaluation of bridge members and the structural global reliability can be accomplished, providing the possibilities of quantitative seismic performance assessment and earthquake resistance optimization design from an overall perspective. Highlights: A global reliability evaluation strategy of high-pier bridges is proposed. Stochastic model for multi-point multi-component ground motions is presented. Unified expression of SRM and POD for non-stationary vector process is derived. Dimension-reduction is developed for multi-point multi-component ground motions. Probability density evolution of a high-pier long-span bridge is performed.